อานิสงส์แห่งนิโรธสมาบัติ - ปักสังขาเนย์, เตชทัต (วารสารศรีล้านช้างปริทรรศน์, 2016)
นิโรธสมาบัติ เป็นความสามารถพิเศษสำหรับพระอรหันต์และพระอนาคามีผู้ได้ฌานสมาบัติเท่านั้น ผู้ที่เข้านิโรธสมาบัติจะได้รับความสุขอันเกิดจากความสงบแห่งจิตอย่างสูงสุดกระทั่งลืมกินลืมพักผ่อน แต่ธรรมชาติของร่างกายมนุษย์ที่ต้องมีการดื่ม การกิน การขับถ่าย การพักผ่อน การเคลื่อนไหวอิริยาบถต่าง ๆ ท่านที่เข้านิโรธสมาบัติจึงไม่อาจอยู่ในสภาวะนั้น ๆ ได้นานเกินกว่าที่ร่างกายจะทนไหว เพราะร่างกายจะถูกทำลายหรือเสื่อมสลายลงเพราะขาดน้ำขาดอาหาร จึงมีตำนานเล่ากันต่อ ๆ มาว่า ผู้ที่ถวายอาหารมื้อแรกแด่ท่านผู้ออกจากนิโรธสมาบัติจะได้รับอานิสงส์ในปัจจุบันทันตา ฟังดูเป็นเรื่องเหลือเชื่องมงาย แต่เรื่องของจิตเป็นสิ่งที่ยังรอคอยการพิสูจน์เพื่อความกระจ่างอยู่ตลอดเวลา           Nirodha Samapatti was praised as an extraordinary ability only for Arahants and Anagamis who attained Jhana Samapatti. Whoever attained Nirodha Samapatti experienced happiness from tranquility until he forgot to have food or to get some sleep while human bodies naturally needed drinking water, food, excretion, sleep, and body movement. So, he could not stay in Nirodha Samapatti longer than his body could endure because his body would be destroyed due to lack of water and food. In addition, there were several stories on any person who gave the first meal to who released from Nirodha Samapatti had got an urgent advantage here and now. It sounded unbelievable and credulous, but everything about human minds always waited for the scientific proof.